Lessons from the masters : current concepts in astronomical image processing - Gendler, Robert (The Patrick Moore Practical Astronomy Series, 2013)
There are currently thousands of amateur astronomers around the world engaged in astrophotography at increasingly sophisticated levels. Their ranks far outnumber professional astronomers doing the same and their contributions both technically and artistically are the dominant drivers of progress in the field today. This book is a unique collaboration of individuals, all world-renowned in their particular area, and covers in detail each of the major sub-disciplines of astrophotography. This approach offers the reader the greatest opportunity to learn the most current information and the latest techniques directly from the foremost innovators in the field today.   The book as a whole covers all types of astronomical image processing, including processing of eclipses and solar phenomena, extracting detail from deep-sky, planetary, and widefield images, and offers solutions to some of the most challenging and vexing problems in astronomical image processing. Recognized chapter authors include deep sky experts such as JAY GABANY, TONY HALLAS, ROBERT GENDLER, KEN CRAWFORD, high-resolution planetary expert DAMIAN PEACH, and the founder of The World at Night BABAK A. TAFRESHI, among other luminaries in the field of astronomical image processing.   A large number of quality illustrations help explain the critical concepts and complex techniques the modern astrophotographer will need to achieve the highest level of quality in their astronomical images.